Pre-Service Teachers’ Soft Skills and Achievement - et. al., Lamhot Naibaho, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to identify pre-service teachers' skills and achievement. This study was done at Universitas Kristen Indonesia. A total of 94 pre-service teachers’ who were in the seventh semester at the faculty of education and teacher training Universitas Kristen Indonesia participated in this study. This study was a quantitative study with survey design. Data were collected using a questionnaire. The results of the study show that the level of soft skills of Pre-service English foreign language Teachers is at an excellent level. The results of the study also show that there is a positive relationship between pre-service teachers' skills and achievement. Besides, the findings also show that there is a significant difference between skills and achievement. In conclusion, the importance of teamwork, willingness to take responsibility and collaborative learning are among the essential aspects for effective learning in this context that teachers need to think. Finally, this study suggests several initiatives that can be done, especially those related to the pre-service teachers’ skills and achievement to improve the marketability of graduates.